Effect of the Melt Pool Boundary Network on the Anisotropic Mechanical Properties of Selective Laser Melted 304L - Myranda Spratt; Joseph W. Newkirk; Okanmisope Fashanu; K. Chandrashekhara (Journal of Manufacturing and Materials Processing, 2021)
Anisotropic mechanical properties are a well-known issue in selective laser melted parts. The microstructure produced by selective laser melting (SLM) is directional, including the solidified melt pool structures and grains. This work investigates the melt pool boundary’s effects on 304L stainless steel’s compressive properties. 304L stainless steel solid cylinders were built using a pulse laser SLM machine in four directions using three hatch angle rotations: 0°, 67°, and 105°. The twelve samples were compression tested, and the results were analyzed. Numerical models were also created with the different hatch angles and directions. The melt pool boundary network (MPBN) in each build was tracked using the model across multiple planes. Results showed that both the hatch angle and build orientation influenced the concentration of melt pool boundaries present in the manufactured samples. A weak negative correlation of compressive strength to the melt pool boundaries’ concentration was also observed, indicating that the melt pool boundary concentration negatively affected the material’s strength. Local anisotropic plastic deformation was also observed in some of the compressed samples. In those samples, it was observed that directions that plastically deformed more also contained higher concentration of the melt pool boundaries.